(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
This article examines the historical development and implementation of information technologies in physical education and sports. Through comprehensive analysis of scientific literature and online sources, the study explores early innovations in computer programs and software applications designed for biomechanical analysis, monitoring of physical condition, training modeling, and individualized program creation in sports and fitness. Key contributions from researchers at the National University of Physical Education and Sports of Ukraine are highlighted, including significant developments in posture analysis, foot diagnostics, and video-based motion capture systems. The paper thoroughly reviews specialized software for professional bodybuilding, aqua aerobics, family health management, and student physical education, demonstrating the breadth of applications across various domains. A detailed classification system for information technologies in physical culture and sports is presented, categorizing applications by areas such as sports training, physical education, and rehabilitation. The research demonstrates the widespread adoption of information technologies across diverse aspects of physical education and sports, enabling sophisticated biomechanical assessments, comprehensive physical state monitoring, advanced training simulations, and personalized program development. The authors conclude that information technologies have become integral tools in enhancing physical education and sports practices, with significant potential for further implementation in higher education curricula. The study also emphasizes the need for continued research and development in this rapidly evolving field, particularly in areas such as virtual reality applications and mobile technologies for promoting physical activity and health.